Ventral hippocampal cholecystokinin interneurons gate contextual reward memory - Robin Nguyen; Sanghavy Sivakumaran; Evelyn K. Lambe; Jun Chul Kim (iScience, 2024)
Summary: Associating contexts with rewards depends on hippocampal circuits, with local inhibitory interneurons positioned to play an important role in shaping activity. Here, we demonstrate that the encoding of context-reward memory requires a ventral hippocampus (vHPC) to nucleus accumbens (NAc) circuit that is gated by cholecystokinin (CCK) interneurons. In a sucrose conditioned place preference (CPP) task, optogenetically inhibiting vHPC-NAc terminals impaired the acquisition of place preference. Transsynaptic rabies tracing revealed vHPC-NAc neurons were monosynaptically innervated by CCK interneurons. Using intersectional genetic targeting of CCK interneurons, ex vivo optogenetic activation of CCK interneurons increased GABAergic transmission onto vHPC-NAc neurons, while in vivo optogenetic inhibition of CCK interneurons increased cFos in these projection neurons. Notably, CCK interneuron inhibition during sucrose CPP learning increased time spent in the sucrose-associated location, suggesting enhanced place-reward memory. Our findings reveal a previously unknown hippocampal microcircuit crucial for modulating the strength of contextual reward learning.